2019
DOI: 10.1016/j.sajb.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

An insight into antidiabetic properties of six medicinal and edible mushrooms: Inhibition of α-amylase and α-glucosidase linked to type-2 diabetes

Abstract: As a continuation of our search for biologically active mushroom species the present study investigates in vitro antidiabetic properties of six edible and medicinal mushroom species: Agaricus blazei Murrill, Coprinus comatus (O.F.Müll.) Pers., Cordyceps militaris (L.) Fr., Inonotus obliquus (Ach. ex Pers.) Pilát, Morchella conica Pers. and Phellinus linteus Berk. & M.A. Curtis. In vitro assays on α-amylase and α-glucosidase enzyme inhibition were performed with methanolic extracts of the selected mushrooms. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…On the other hand, inhibition of carbohydrate digesting enzymes such as α‐amylase or α‐glucosidase have been earmarked as the main target to control postprandial glucose peak in type 2 diabetics patients [22,23] . In this respect, several inhibitors (tacrine and donepezil for Alzheimer's disease; acarbose and voglibose for type 2 diabetes) have been synthetically developed in an attempt to control the afore‐mentioned ailments.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, inhibition of carbohydrate digesting enzymes such as α‐amylase or α‐glucosidase have been earmarked as the main target to control postprandial glucose peak in type 2 diabetics patients [22,23] . In this respect, several inhibitors (tacrine and donepezil for Alzheimer's disease; acarbose and voglibose for type 2 diabetes) have been synthetically developed in an attempt to control the afore‐mentioned ailments.…”
Section: Introductionmentioning
confidence: 99%
“…2 It has been well demonstrated that wild mushrooms are one of the most important functional foods and good sources of nutraceuticals. 3,4 The fungi of the genus Macrolepiota belong to the family Agaricaceae (Basidiomycota). Besides the pleasant taste, Macrolepiota species are also known for their nutritional value.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the control of blood glucose level is a critical method to prevent the progression of type 2 diabetes and its complications (Martinez, Lockhart, Davies, Lindsay, & Dempster, ). In consideration of limitations and negative side effects of commercial chemosynthetic drugs, numerous scientific investigations are being incessantly conducted into various natural products, including triterpenoids (Khanra et al, ) and flavonoids (Tanveer, Akram, Farooq, Hayat, & Shafi, ), which have a preventive or therapeutic effect on diabetes (Stojkovic et al, ; Thompson & Davis, ). Therefore, dietary therapies targeting the origin of insulin resistance are preferable for the prevention of diabetes.…”
Section: Introductionmentioning
confidence: 99%